The effect of the perceived social support on mental health of Chinese college soccer players during the COVID-19 lockdown: The chain mediating role of athlete burnout and hopelessness - Zhao, Liangyu; Liu, Zongyu; Zhang, Liguo (Frontiers in Psychology, 2022)
The isolation and blockade during the COVID-19 pandemic have a great impact on the mental health of Chinese college soccer players. This study aimed to explore the effect of perceived social support on mental health of college soccer players, as well as the mediating role of athlete burnout and hopelessness during the COVID-19 lockdown. Based on a sample of 674 college soccer players from several universities in China, the study used the Perceived Social Support Scale (PSSS), Kessler Psychological Distress Scale (K10), Athlete Burnout Questionnaire (ABQ) and Beck Hopelessness Scale (BHS). The results indicated that: (1) there was a significant positive correlation between perceived social support and mental health of college soccer players; (2) the athlete burnout played a mediating role between perceived social support and mental health of college soccer players; (3) the hopelessness also played a mediating role between perceived social support and mental health of college soccer players; (4) the athlete burnout and hopelessness played a chain mediating role between perceived social support and mental health. These findings could contribute to insight into the mechanisms by which perceived social support affects the mental health of college soccer players and provide important practical guidance for protecting and promoting their mental health.